Phenotypic plasticity and the colonization of new habitats : A study of a colonial spider in the Chaco region and the Cerrado - Fernández Campón, F. (2021)
In social animals, group prey capture could facilitate colonization of new areas with low resource availability. Parawixia bistriata is a colonial spider inhabiting seasonal dry forests and mesic habitats in South America. Individuals capture prey as a group, which allows individuals to broaden their foraging niche by incorporating large prey that cannot be subdued in solitary captures. P. bistriata exhibits two behavioural ecotypes a “dry” (plastic) ecotype which modifies individual’s tendency to capture prey in a group depending on food resources and a “wet” (fixed) ecotype, whose tendency to group prey capture is only modulated by the size of the prey but not by prey availability. By reconstructing the range expansion of the species using phylogeographic and species distribution modelling techniques, we indirectly examined whether group prey capture could have helped P. bistriata in colonization of low resource habitats. Based on cytochrome c oxidase subunit I gene genealogy, we found older populations in northern Cerrado in Brazil with more recent populations located further south in Dry and Humid Chaco in Argentina, with the latter being the most derived. Species distribution modelling for each ecotype suggests that suitable habitat for each ecotype started to overlap at some point during the Last Glacial Maximum (21 ky BP). These results suggest that P. bistriata expanded from northern Cerrado south to the Gran Chaco, being able to colonize mesic habitats at a later stage when individuals reached southern territories in the Chaco. This evidence is opposite to the idea that GPC facilitated P. bistriata colonization from mesic to harsher environments. However, plasticity in group prey capture could have been important to allow individuals to establish in mesic habitats by reducing the cost of group capture when under high resource levels.